New Physics and Schmitt’s Work: The Play of "Einstein’s Treason" - Amirian, Simin; Yousof, Ghulam Sarwar (Journal of History Culture and Art Research, 2017)
Humankind has walked many roads to achieve understanding of themselves and to discover their own nature as God's creation. The cognition of humanity, God, and nature is a permanent, pervasive issue throughout history. In this quest to discover humanity, the fields of philosophical anthropology and biological anthropology have emerged and developed alongside each other. Science and philosophy are also trying to find a way to explain creation with all various products created throughout the history. But the noticeable point is the fact that a number of play writers have stepped in to ease the way for a better understanding of complicated concepts such as theology and anthropology in regard to philosophy and physics, and help to facilitate this understanding by creating literary work. Eric-Emmanuel Schmitt (1960) as a contemporary writer had focused his attention on the achievements of science and new physic in recent decades. His works invites the audience to think and contemplate on meaning and, once again, raise issues of human existence and life’s meaningful activities. This paper attempts to investigate Eric-Emmanuel Schmitt as a modern dramatist through a detailed, qualitative and critical analysis of one of his most important works, Einstein’s Treason. In Einstein’s Treason, physics and Einstein's life has been used widely. The study explored how the concept of new physics and quantum theory could be incorporated in to literature of drama in Einstein’s Treason.